2017
DOI: 10.1111/papt.12153
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic day treatment programme for patients with schizophrenia spectrum disorders: Dynamics and predictors of therapeutic change

Abstract: A psychodynamically based group programme improves the clinical status and quality of life in patients with schizophrenia spectrum disorders. Data indicate that changes on the subjective level are detectable by the end of the programme, while changes on the objective level are detectable at follow-up assessment. Symptom severity and working or study activities are positively related to the clinical improvement in this type of programme, while a high number of years in psychiatric treatment or psychiatric hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Patients improved significantly during the 2 years of treatment with moderate to strong effect sizes on positive and negative symptoms, general symptom level, and social function. In line with these findings, other studies found support for improved symptomatology along with changes in some cognitive/social functioning, and quality of life of patients with schizophrenia receiving long-term (up to 3 years) psychodynamic group therapy in addition to regular antipsychotic treatment (Restek-Petrović et al, 2014; Pec et al, 2018).…”
Section: Psychodynamic Psychotherapy and Psychopharmacology Of Mentalmentioning
confidence: 61%
“…Patients improved significantly during the 2 years of treatment with moderate to strong effect sizes on positive and negative symptoms, general symptom level, and social function. In line with these findings, other studies found support for improved symptomatology along with changes in some cognitive/social functioning, and quality of life of patients with schizophrenia receiving long-term (up to 3 years) psychodynamic group therapy in addition to regular antipsychotic treatment (Restek-Petrović et al, 2014; Pec et al, 2018).…”
Section: Psychodynamic Psychotherapy and Psychopharmacology Of Mentalmentioning
confidence: 61%
“…Recently, years of psychiatric treatment, number of psychiatric hospitalizations, number of suicide attempts, and the experience of a partnership were found as negative predictors. Actual work or study activities were found as positive predictors related to clinical improvement in a psychodynamic day treatment program 44 …”
Section: Discussionmentioning
confidence: 94%
“…Actual work or study activities were found as positive predictors related to clinical improvement in a psychodynamic day treatment program. 44 On the other hand, the connection can tell us more about how to understand the process of recovery. Psychotherapeutic services are not always available in community settings, but people with psychoses are engaged in supporting relationships.…”
Section: Threshold From Awareness To Preparation or Rebuilding Phasementioning
confidence: 99%
“…In literature, there are not many studies on follow-up children and adolescents in day treatment. Studies are especially about adult patients with diagnosed schizophrenia or substance use disorders (27,28). As studies that compares day treatments and inpatient units; day treatment has been shown to reduce stigmatization.…”
Section: Discussionmentioning
confidence: 99%